Practitioners' guide to human rights law in armed conflict - Murray, Daragh; Akande, Dapo (Oxford, United Kingdom : London : Oxford University Press Royal Institute of International Affairs (Chatham House), 2016)
"Although the relationship between international human rights law and the law of armed conflict has been the subject of significant recent academic discussion, there remains a lack of comprehensive guidance in identifying the law applicable to specific situations faced by military forces. Providing guidance for armed forces and practitioners on the detailed application of international human rights law during armed conflict, this book fills that gap. Part 1 of the volume details foundational information relating to international human rights law and human rights institutions, the types of operations that States' armed forces engage in, and how the law of armed conflict and international human rights law apply to regulate different situations. Part 2 provides practical guidance as to the legal regulation of specific situations, including discussion of the conduct of hostilities, detention operations, humanitarian assistance, cyber operations, and investigations"--Publisher's website.
Introduction -- Part I. -- Understanding international human rights law -- Identifying, defining, and classifying the activities of armed forces -- The extra-territorial applicability of international human rights law -- The relationship between the law of armed conflict and international human rights law -- Part II. -- Conduct of hostilities and targeting -- Rules of Engagement -- Weapons -- Prisoners of war and internment -- Protection of civilians in the hands of a party to the conflict -- Occupation -- Peace support operations -- Humanitarian assistance -- Air operations -- Maritime warfare -- Cyber operations -- Multinational operations -- Enforcement.
Includes bibliographical references and index.
Keywords: War (International law); International law and human rights; Human rights; Human rights; International law and human rights; War (International law); Law